'Smiles and laughter and all those really great things': Nurses' perceptions of good experiences of care for inpatient children and young people with intellectual disability. (22nd April 2022) - Mimmo, Laurel; Hodgins, Michael; Samir, Nora; Travaglia, Joanne; Woolfenden, Susan; Harrison, Reema
Abstract: Aim: To understand what constitutes a good experience of care for inpatient children and young people with intellectual disability as perceived by nursing staff. Design: Interpretive qualitative study. Methods: Focus groups with clinical nursing staff from speciality neurological/neurosurgical and adolescent medicine wards across two specialist tertiary children's hospitals in Australia were conducted between March and May 2021. Data analysis followed interpretative analysis methods to develop themes and codes which were mapped to a conceptual model of safe care. Results: Six focus groups with 29 nurses of varying experience levels were conducted over 3 months. Themes and codes were mapped to the six themes of the conceptual model: use rapport, know the child, negotiate roles, shared learning, build trust and relationships, and past experiences. The analysis revealed two new themes that extended the conceptual model to include; the unique role of a paediatric nurse, and joy and job satisfaction, with a third contextual theme, impacts of COVID‐19 pandemic restrictions. With the perspectives of paediatric nurses incorporated into the model we have enhanced our model of safe care specifically for inpatient paediatric nursing care of children and young people with intellectual disability. Conclusion: Including perceptions of paediatric nurses confirmed the position of the child with intellectual disability being at the centre of safe care, where care is delivered as a partnership between nursing staff, child or young person and their parents/family and the hospital systems and processes. Impact: The enhanced model offers a specialized framework for clinical staff and health managers to optimize the delivery of safe care for children and young people with intellectual disability in hospital.